2022
DOI: 10.1021/acs.estlett.2c00107
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic and Nanoplastic Interactions with Plant Species: Trends, Meta-Analysis, and Perspectives

Abstract: The ubiquitous presence of nanoplastics (NPx) and microplastics (MPx) in the environment has been demonstrated, and as such, the exposure scenarios, mechanisms of plant response, and ultimate risk must be determined. Here, we performed a meta-analysis of the most recent literature investigating the effect of MPx/NPx on plant species under laboratory and field conditions so as to evaluate the current state of knowledge. Effects of MPx/NPx exposure in plants vary as a function of plant species, and interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…However, most of the current information on the effects of NPs on the physiology of higher plants is negative, which may be related to the fact that most studies set too high concentrations of NPs (Dong et al, 2020; Gao et al, 2021; Wang, Lin, et al, 2022). Similar findings were demonstrated in another meta‐analysis where a significant correlation was found between the biological effects of NPs and NP concentration (Azeem et al, 2022). Undoubtedly, NPs above the threshold concentration will cause significant negative effects on plant growth (more information in the next section).…”
Section: Effects Of Nps On Plant Growthsupporting
confidence: 87%
See 1 more Smart Citation
“…However, most of the current information on the effects of NPs on the physiology of higher plants is negative, which may be related to the fact that most studies set too high concentrations of NPs (Dong et al, 2020; Gao et al, 2021; Wang, Lin, et al, 2022). Similar findings were demonstrated in another meta‐analysis where a significant correlation was found between the biological effects of NPs and NP concentration (Azeem et al, 2022). Undoubtedly, NPs above the threshold concentration will cause significant negative effects on plant growth (more information in the next section).…”
Section: Effects Of Nps On Plant Growthsupporting
confidence: 87%
“…Plastics are widely used in everyday life due to their excellent properties and low cost (Azeem et al, 2022; Dissanayake et al, 2022). Global annual plastic production has increased from 1.5 million tons in 1950 to 390.7 million tons in 2021 (PlasticsEurope, 2022), which is even expected to exceed 33 billion tons by 2050 (Lau et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the classical approach with either mass concentration or size alone fails to explain plant responses. In line with us, Azeem et al reported that particle size and dose of micro­(nano)­plastics had multiple effects on plants . In subsets of data with dilute suspensions of nanoplastics, total surface area or specific surface area of nanoplastics had the potential to reveal hidden relationships that were not targeted in the original investigations (Figure S3).…”
Section: Resultsmentioning
confidence: 62%
“…In line with us, Azeem et al reported that particle size and dose of micro(nano)plastics had multiple effects on plants. 28 In subsets of data with dilute suspensions of nanoplastics, total surface area or specific surface area of nanoplastics had the potential to reveal hidden relationships that were not targeted in the original investigations (Figure S3). Linear relationships were established when the effect sizes of morphological functions or root length were plotted against total surface area (Figure S3a,b) or when the effect sizes of MDA content and CAT and SOD activities were plotted against specific surface area (Figure S3c−e and Text S3).…”
Section: Resultsmentioning
confidence: 99%
“…Plastic pollution in freshwater and on land continues to increase and threaten the health of humans and ecosystems (Azeem et al 2022;Dhaka et al 2022;Larue et al 2021;Vethaak and Legler 2021). Currently, there are major concerns about small fragments produced from the degradation of large plastic debris (Boyle and Ormeci 2020;John et al 2022;Mu et al 2022;Sharma et al 2021).…”
Section: Higher Reactivitymentioning
confidence: 99%